MINORITY GROUP IN URBAN SOCIETY CONFLICT AND THREATS TO RELIGIOUS FREEDOM A CASE STUDY OF SYMBOLIC VIOLENCE AGAINST AHMADIYYA IN URBAN SOCIETY - Barsihannor Barsihannor; Gustia Tahir; Haslinda Binti Hasan (Akademika : Jurnal Pemikiran Islam, 2023)
This study explores the experiences of the Ahmadiyya Muslim community in the context of urban society, focusing on the manifestation of symbolic violence against this minority group and its implications for religious freedom. Symbolic violence encompasses various forms of discrimination, prejudice, and non-physical harm that target religious minorities. This research delves into the multifaceted dynamics surrounding the Ahmadiyya community's presence in urban areas and how they navigate challenges related to their faith and religious identity. The study is qualitative. The data were collected through online questionnaires and in-depth interviews with the Ahmadiyya congregations in three urban society as representatives of Indonesia namely Bandung (West Java), Makassar (South Sulawesi) and Lombok (West Nusa Tenggara) with the aim to examine the nature of symbolic violence against the Ahmadiyya community in urban society, highlight the broader implications for religious freedom in diverse societies as well as to find out the principle ​​adhered by the Ahmadiyya group in maintaining its existence amid the pressure of the transnational radical Islamic groups. The research results show that apart from experiencing physical violence, the Ahmadiyya followers also experienced symbolic violence whose impacts were felt to be much more painful than physical violence. The symbolic violence occurs in Capital and Habitus domain. Despite undergoing the acts of violence, the Ahmadiyya congregation is still able to survive by adhering to the values that have been their principle, that is “Love for all and hatred for none”.